Enzymatic formation of galactooligosaccharides in goat milk. (December 2018) - Zhu, Fan; Prosser, Colin; Zhu, Ying; Otter, Don; Hemar, Yacine
Abstract: Goat milk has become more popular due to its attractive nutritional profile. Galactooligosaccharides (GOS) are prebiotics with health benefits. The enzymatic formation of GOS in reconstituted goat milk using two commercial β-galactosidases (L6500 from Kluyveromyces lactis and L10 from Aspergillus oryzae ) was studied. The carbohydrate composition of the milk system was quantified using high-performance anion-exchange chromatography. Major GOS produced by β-galactosidases under the experimental conditions (45 °C, pH 6.7) were 6-galactobiose, allolactose, and 6-galactosyllactose. The maximum GOS yields in goat milk with 10% total solids were obtained when the lactose conversion rates were 59% for L10 and 88% for L6500. Further increasing lactose conversion decreased GOS formation. Increasing milk concentration from 10% to 30% total solids (lactose concentration from 47 to 143 g/L) increased GOS yields up to 22% of the total sugars using L6500. It may be concluded that suitable experimental conditions can be used to produce GOS in goat milk with prebiotic function.